2007
DOI: 10.2466/pr0.100.3.721-726
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism, Extraversion, and Paralinguistic Expression

Abstract: The purpose of this study was to test the associations among neuroticism, extraversion, and paralinguistic expression. The relevant literature provides ample information on the association between personality traits and voice intensity, pitch, pace of speaking, frequency of pauses, slips of the tongue, and other speech impediments. The author attempted to verify and supplement work reported previously. Scores for 100 persons (56 women, 44 men; M age =21.5 yr., SD= 1.5) were analyzed with respect to two aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
0
10
0
5
Order By: Relevance
“…Furthermore, Neuroticism is related to nonverbal qualities of appearance and behavior; Borkenau and Liebler (1995) found that more neurotic targets behaved less positively overall (e.g., less smiling) and behaved in an uncertain and nondominant manner (e.g., less self-assured expression, less eye contact, less powerful voice, and more speech dysfluencies). Other studies have found that Neuroticism is linked to behavioral signs of anxiety or nervousness (Back, Schmukle, & Egloff, 2009;Gawda, 2007;Hirschm€ uller, Egloff, Schmukle, Nestler, & Back, 2015).…”
Section: Distressed Affect and Neuroticismmentioning
confidence: 96%
“…Furthermore, Neuroticism is related to nonverbal qualities of appearance and behavior; Borkenau and Liebler (1995) found that more neurotic targets behaved less positively overall (e.g., less smiling) and behaved in an uncertain and nondominant manner (e.g., less self-assured expression, less eye contact, less powerful voice, and more speech dysfluencies). Other studies have found that Neuroticism is linked to behavioral signs of anxiety or nervousness (Back, Schmukle, & Egloff, 2009;Gawda, 2007;Hirschm€ uller, Egloff, Schmukle, Nestler, & Back, 2015).…”
Section: Distressed Affect and Neuroticismmentioning
confidence: 96%
“…(1974), have also convincingly demonstrated the existence of an individual rhythm of speech that does not depend on the verbal task. While trying to confirm the previous findings, Gawda B. (2007) found a correlation between extroversion and neuroticism, on the one hand, and fluency of speech on the other.…”
Section: Psychological Research Of the Intonation Phenomena Of Speechmentioning
confidence: 59%
“…A more recent account of the state-of-the-art, especially on the automatic recognition of personality with the help of speech and linguistic information, and experimental results can be found in (Mairesse et al, 2007). To give some examples of other topics: Gawda (2007) tests the associations among neuroticism, extraversion, and paralinguistic expression. Hirschberg (2005, 2009) deal with acoustic/prosodic and lexical correlates of charismatic speech.…”
Section: Paralinguistic Analysis: An Overviewmentioning
confidence: 99%